PERCEIVED IMPACT OF PARTICIPATION IN FOREST MANAGEMENT ON NATURAL AND SOCIAL CAPITALS IN MANSEHRA DISTRICT OF PAKISTAN - B. Shahbaz; T. Ali; M. Awais (Journal of Animal and Plant Sciences, 2012)
The paradigm shift in forest governance – from top-down bureaucratic to participatory approach – in many developing countries was made during the nineties in response to the high deforestation and inefficiency of state institutions for sustainable forest governance. In the mountainous region of Khyber Pakhtunkhwa province of Pakistan (previously known as North West Frontier Province, NWFP) the process of institutional changes in forestry sector was also started in the mid nineties and now participation to local stakeholders has become a significant feature of the forest policy of the province. To confer practical look to the participatory forestry, village level institutions were established in the selected villages for the management of forests and carrying out developmental activities. In this milieu, this paper attempts to assess the net correlation between participation in forest management and livelihood assets of the forest dwellers by using sustainable livelihoods framework. The results showed that there was positive relationship (net correlation) between participation and the access of the respondents to social and natural assets, but other livelihood assets (financial, human and physical) remained unchanged. It is recommended that sustainable management of forest resources necessitates that the forest conservation initiatives should be coupled with the enhancement of financial and human capital of the communities living in or around forest areas.
Keywords: Sustainable forest management; Participatory approach; Livelihood assets; Social Capital; Northwest